Fractal calculus for analysis of wool fiber: Mathematical insight of its biomechanism - Fan, Jie; Yang, Xue; Liu, Yong (Journal of engineered fibers and fabrics, 2019)
Wool fiber has a complex hierarchic inner structure. However, like most of the natural things, wool fiber does not have an exactly strict self-similar fractal feature. Here, we calculate the fractal dimension of each hierarchic level of wool fiber using the two-scale dimension method. The obtained fractal dimension of wool fiber in different hierarchic level ranges between 1.37 and 1.47, which is close to that obtained according to the traditional fractal geometry. Thermal property of wool fiber is investigated based on the fractal feature of wool fiber. The result shows that the temperature gradient and the rate of the temperature gradient along the fiber is very slow, suggesting that wool fiber has a good thermal retention property.